2012
DOI: 10.1002/ctpp.201200044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Chemical Study of a RF Discharge Containing Aluminum Tri‐Isopropoxide Using MIR Absorption Spectroscopy Based on External‐Cavity Quantum Cascade Lasers

Abstract: In Ar and Ar/N 2 RF plasmas with admixtures of aluminum tri-isopropoxide (ATI) the fragmentation of this metal-organic precursor has been studied by means of infrared absorption spectroscopy (IR-AS) using an external-cavity quantum cascade laser (EC-QCL) arrangement. The experiments were performed in an asymmetric capacitively coupled reactor at a frequency of f = 13.56 MHz and a pressure of up to p = 10 Pa. The discharge power was in the range of P = 40 -100 W. Using EC-QCLAS the evolution of the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The volume of the entire reactor configuration was 60 l. A more detailed description of the experimental setup can be found in [17]. Figure 1 shows a drawing of the setup with FTIR diagnostics.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The volume of the entire reactor configuration was 60 l. A more detailed description of the experimental setup can be found in [17]. Figure 1 shows a drawing of the setup with FTIR diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…CH 4 , C 2 H 2 and C 2 H 4 , have been part of a former study [17], which was performed under the same experimental conditions. While the concentration range is comparable, it is interesting to note that Lopatik and co-workers found that the concentration of C 2 H 2 and C 2 H 4 decreases with power.…”
Section: Ati Behaviour As a Function Of The Mixing Ratio Experimentsmentioning
confidence: 99%
See 3 more Smart Citations